Regulation of gene expression by the action of a fungal lncRNA on a transactivator. Issue 1 (2nd January 2020) - Till, Petra; Derntl, Christian; Kiesenhofer, Daniel P; Mach, Robert L; Yaver, Debbie; Mach-Aigner, Astrid R
ABSTRACT: Long non-coding RNAs (lncRNAs) are crucial factors acting on regulatory processes in eukaryotes. Recently, for the first time in a filamentous fungus, the lncRNA HAX1 was characterized in the ascomycete Trichoderma reesei . In industry, this fungus is widely applied for the high-yield production of cellulases. The lncRNA HAX1 was reported to influence the expression of cellulase-encoding genes; interestingly, this effect is dependent on the presence of its most abundant length. Clearly, HAX1 acts in association with a set of well-described transcription factors to regulate gene expression. In this study, we attempted to elucidate the regulatory strategy of HAX1 and its interactions with the major transcriptional activator Xylanase regulator 1 (Xyr1). We demonstrated that HAX1 interferes with the negative feedback regulatory loop of Xyr1 in a sophisticated manner and thus ultimately has a positive effect on gene expression.